2006
DOI: 10.1007/s00535-006-1815-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the hemodynamics of rectal varices by endoscopic ultrasonography

Abstract: The velocities of rectal varices were lower than those of esophageal varices. Evaluation of the hemodynamics of rectal varices is important for determining the appropriate therapeutic option. EIS is an effective therapy in cases of slow variceal flow. ECDUS is a necessary tool for effective and safe EIS for rectal varices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…ECDUS can detect anorectal varices through colour flow images, and it facilitates more detailed observation of the hemodynamics of rectal varices than conventional EUS [31]. In addition, ECDUS may be helpful in risk stratifying anorectal varices through measurement of the velocity of blood flow within a varix; Sato et al demonstrated a significantly higher mean velocity of blood flow in the rectal varices of patients experiencing acute bleeding compared to patients who did not experience bleeding [32].…”
Section: Endoscopic Ultrasound (Eus)mentioning
confidence: 99%
See 1 more Smart Citation
“…ECDUS can detect anorectal varices through colour flow images, and it facilitates more detailed observation of the hemodynamics of rectal varices than conventional EUS [31]. In addition, ECDUS may be helpful in risk stratifying anorectal varices through measurement of the velocity of blood flow within a varix; Sato et al demonstrated a significantly higher mean velocity of blood flow in the rectal varices of patients experiencing acute bleeding compared to patients who did not experience bleeding [32].…”
Section: Endoscopic Ultrasound (Eus)mentioning
confidence: 99%
“…In addition, ECDUS may be helpful in risk stratifying anorectal varices through measurement of the velocity of blood flow within a varix; Sato et al demonstrated a significantly higher mean velocity of blood flow in the rectal varices of patients experiencing acute bleeding compared to patients who did not experience bleeding [32]. Endoscopic treatments such as injection sclerotherapy can also be performed with ECDUS, which can assess efficacy by a reduction in the velocity of blood flow in rectal varices following injection [33].…”
Section: Endoscopic Ultrasound (Eus)mentioning
confidence: 99%
“…They also showed that the mean velocity of blood flow in rectal varices in the patients with rectal bleeding was significantly higher than in those cases experiencing no bleeding which indicates that the color doppler ultrasonography may be helpful in identifying highrisk group for rectal variceal rupture via the measurement of velocity [20] . Endoscopic color Doppler ultrasonography is better equipped than conventional EUS to evaluate the hemodynamics of varices, it can detect rectal varices through color flow images, calculate the velocity of blood flow in rectal varices for an effective and safe endoscopic variceal management [21] .…”
Section: Endoscopic Ultrasoundmentioning
confidence: 99%
“…On the other hand, conventional EUS (7.5 or 12 MHz) reveals rectal varices as rounded, oval, or longitudinal echo-free structures in the submucosa and also shows perirectal veins outside the rectal wall (4,9,10). With endoscopic color Doppler ultrasonography (ECDUS), color flow images in blood vessels can be obtained, and ECDUS allows for more detailed observation of the hemodynamics of rectal varices than EUS (11). CDUS is a simpler, more non-invasive method than ECDUS and it enables us to detect slight blood flow and to evaluate the portal venous system.…”
Section: Diagnosis Of Rectal Varicesmentioning
confidence: 99%
“…ECDUS is better equipped than conventional EUS to visualize in detail the hemodynamics of esophagogastric varices (17,18). With ECDUS, color flow images in blood vessels can be obtained, and ECDUS allows for more detailed observation of the hemodynamics of rectal varices than EUS (11). ECDUS is useful for detecting rectal varices through color flow images, and it is a necessary tool for effective and safe EIS by calculating the velocity of blood flow in rectal varices (Fig.2).…”
Section: Diagnosis Of Rectal Varices Via Endoscopic Ultrasonography (mentioning
confidence: 99%